A CEBOCEPHALUS (CYCLOPIA) MONSTER IN A CROSS-BRED COW - KHASATIYA, C T (The Indian Journal of Animal Reproduction, 2010)
A cebocephalus / cyclopia monster with epitheliogenesis imperfecta over the forehead and body,having rudimentary and separate eye balls and atypical deformed ears and jaw was delivered bytraction in an HF crossbred cow.
Keywords: Monster; Cebocephalus; Dystocia; Cow